RNA Interference Therapeutics in Cardiology: Focus on Zilebesiran and Olpasiran - Skibicka, Katarzyna; Skibicki, Tomasz; Wesołowska, Weronika; Pietrzak, Jarosław (Journal of Education, Health and Sport, 2025)
Background: RNA interference (RNAi) therapeutics represent a novel approach in cardiovascular medicine, enabling durable and selective inhibition of disease-relevant proteins. Objective: This systematic review aimed to evaluate the efficacy, safety, and clinical potential of two leading RNAi therapeutics-zilebesiran for hypertension and olpasiran for elevated lipoprotein(a). Methods: We systematically searched PubMed, Embase, Cochrane Library, and Google Scholar for articles published between January 2018 and June 2025 using the keywords: “RNA interference”, “siRNA”, “zilebesiran”, “olpasiran”, “hypertension”, and “lipoprotein(a)”. Eligible studies included randomized controlled trials (RCTs), systematic reviews, meta-analyses, narrative reviews, and preclinical mechanistic studies in English. Two independent reviewers screened records and extracted data. A total of 20 studies were included: 6 RCTs (Phase 1–2), 5 systematic reviews/meta-analyses, 8 narrative reviews, and 1 preclinical/mechanistic study. Results: Zilebesiran demonstrated sustained blood pressure reduction up to six months with an acceptable safety profile, while olpasiran produced profound and durable decreases in lipoprotein(a) levels, exceeding 90% in phase 2 trials. Safety considerations include long-term tolerability, off-target effects, and accessibility. Emerging reversal agents, such as REVERSIR, may enhance therapeutic safety. Conclusions: RNAi therapeutics hold significant promise in cardiovascular medicine, with zilebesiran and olpasiran addressing major unmet needs. Ongoing large-scale outcome trials are essential to define their role in clinical practice.